The role of the Belarusian State University in the formation of teaching modern and contemporary history of foreign countries in higher educational institutions of Belarus in the 1930–70s - Astroha, Viktar A. (Journal of the Belarusian State University. History, 2021)
The place and role of the department of modern and contemporary history of the faculty of history of the Belarusian State University in the formation and development of teaching modern and contemporary history of foreign countries in various higher educational institutions of Belarus in the period 1930–70s are analysed. The evolution of the department as a leading scientific and educational center in its field is considered. The article describes the work of teachers of the Belarusian State University in the Minsk State Pedagogical Institute named after A. M. Gorky, Vitebsk State Pedagogical Institute named after S. M. Kirov, Republican Party School of the Central Committee of the Communist Party (Bolsheviks) of Belarus, Minsk State Pedagogical Institute of Foreign Languages, Gomel State University and etc. The conclusion is made about the important role of the Belarusian State University in the formation of teaching modern and contemporary history in higher educational institutions of Belarus in the initial period of their activity.
Keywords: Belarusian State University; department of modern and contemporary history of the Belarusian State University; modern and contemporary history of foreign countries; higher educational institutions; teacher; teaching; formation